Implementasi Total Quality Management (TQM) pada Sekolah Berbasis Blended Learning - Puspita Dwi Permatasari; Noor Miyono (Syntax Idea)
This research was conducted at Sekolah Murid Merdeka, Indonesia's first blended learning school, focusing on Total Quality Management (TQM). This study aims to describe and analyze TQM in technology-based schools in addressing the challenges of 21st-century education. The research employs a qualitative approach and descriptive case study method. Data was collected through observations, interviews, and documentation studies involving research subjects such as school development heads, teachers, and program heads at various levels. The results of the study indicate that operational control management and performance measurement are carried out based on the following principles: (1) continuous improvement, (2) establishing quality assurance standards, (3) cultural change, (4) organizational change, and (5) maintaining relationships with customers.